Modern methods for delivery of drugs across the blood-brain barrier - Chen, Yan; Liu, Lihong (Elsevier, 2012)
The blood–brain barrier (BBB) is a highly regulated and efficient barrier that provides a sanctuary to the brain. It is designed to regulate brain homeostasis and to permit selective transport of molecules that are essential for brain function. Unfortunately, drug transport to the brain is hampered by this almost impermeable, highly selective and well coordinated barrier. With progress in molecular biology, the BBB is better understood, particularly under different pathological conditions. This review will discuss the barrier issue from a biological and pathological perspective to provide a better insight to the challenges and opportunities associated with the BBB. Modern methods which can take advantage of these opportunities will be reviewed. Applications of nanotechnology in drug transport, receptor-mediated targeting and transport, and finally cell-mediated drug transport will also be covered in the review. The challenge of delivering an effective therapy to the brain is formidable; solutions will likely involve concerted multidisciplinary approaches that take into account BBB biology as well as the unique features associated with the pathological condition to be treated.